Expertise and collective intelligence: when teams are (and are not) more than the sum of their parts - Williams Woolley, Anita (Henry Stewart Talks, 2013)
Recent research on collective intelligence in human groups, Collective intelligence in animal groups, Background on individual intelligence research in the context of teams, Laboratory studies exploring measurement of collective intelligence in human groups, Key ingredients for intelligent teams, Predictors of collective intelligence in groups, The effects of group gender composition, Social sensitivity and collective intelligence, Cognitive style diversity and collective intelligence, Distribution of communication and collective intelligence, Lab study on group expertise and communication
Reviewed at 2019/05/30